Association between anti-U1 ribonucleoprotein antibodies and inflammatory mediators in cerebrospinal fluid of patients with neuropsychiatric systemic lupus erythematosus. (June 2014) - Yokoyama, T; Fujii, T; Kondo-Ishikawa, S; Yamakawa, N; Nakano, M; Yukawa, N; Yoshifuji, H; Ohmura, K; Mimori, T
Objective: We investigated possible associations between neurotoxic inflammatory mediators (IMs) and anti-U1RNP antibodies (Abs) in cerebrospinal fluid (CSF) of neuropsychiatric systemic lupus erythematosus (NPSLE). Methods: Serum and CSF anti-U1RNP Abs were detected using an RNA-immunoprecipitation assay and CSF anti-U1RNP Ab levels were measured by ELISA. IFN-α, MCP-1 and IL-8 levels in CSF were determined by quantitative multiplex cytokine analysis. IM levels were compared among anti-U1RNP-positive and anti-U1RNP-negative NPSLE as well as other rheumatic disease controls (controls). Results: Anti-U1RNP Abs were detected in serum (58%) and in CSF (18%) of 82 NPSLE patients. CSF MCP-1 levels were higher in NPSLE than in controls. CSF IFN-α level was higher in CSF anti-U1RNP Ab-positive than in -negative patients or controls. When limited to serum anti-U1RNP Ab-positive patients, however, levels of all three IMs in CSF were higher in CSF anti-U1RNP Ab-positive than in -negative patients. Anti-U1RNP Ab levels in CSF correlated with CSF MCP-1, but not IFN-α and IL-8 levels. Conclusions: CSF anti-U1RNP Ab positivity is associated with increased level of CSF IFN-α. MCP-1 levels correlated with CSF anti-U1RNP Ab levels, whereas the increased CSF MCP-1 was not specific to CSF anti-U1RNP Ab-positive NPSLE.